Assessment of Novel Inhaler Technique Reminder Labels in Image Format on the Correct Demonstration of Inhaler Technique Skills in Asthma: A Single-Blinded Randomized Controlled Trial - Iman Basheti; Bassam Mahboub; Laila Salameh; Mena Al-Ani; Ammar Abdulrahman Jairoun; Basema Saddik; Eman Abu-Gharbieh (MDPI AG, 2021)
Background: Prevalence of asthma in the United Arab Emirates (UAE) is high, and training patients on correct inhaler technique is vital. Objectives: To assess the effectiveness of inhaler technique labels incorporating the individual technique steps in image format on the retention of correct inhaler technique for patients with asthma living in the UAE and following inhaler training; secondly to investigate the effect of inhaler technique education using self-check pictorial labels on patients' overall asthma control. Methods: This single-blinded randomized controlled study was conducted in 2019 and followed consecutive recruitment of asthma patients visiting respiratory clinics at Rashid Hospital in Dubai. Patients were using a controller inhaler (Turbuhaler (TH), Accuhaler (ACC), or pressurized metered-dose inhaler (pMDI)). Following recruitment, patients were randomized into active group receiving educational intervention plus the inhaler label, and control group receiving educational intervention without the label. Patients were assessed at baseline and at one-month on their inhaler technique and asthma control. Results: Participants (n = 245; 93 = TH, 70 = ACC, 82 = pMDI) showed a significant difference between the groups at one-month for inhaler technique scores for TH (active 5.29 ± 1.86 vs. control = 24.4 ± 21.28), ACC (active = 3.99 ± 1.43 vs. control = 25.45 ± 22.57), and pMDI (active = 4.59 ± 0.10 vs. control = 120.55 ± 17.2), p < 0.001 for all. Asthma control for active group indicated significant improvements compared to control for TH and pMDI (p < 0.001 for both), but not ACC group (p = 0.087). Conclusions: Retention of correct inhaler technique and improved asthma control can be enhanced by using a specialized inhaler technique label in image format.